Integrating Cloud World Synergy in ELT to Adults: Perspectives of Handheld Technologies - Abugohar, Mohammed Abdulgalil; Yunus, Kamariah; Rabab’ah, Ghaleb; Ahmed, Tarig Awad Eltahir (International Journal of Interactive Mobile Technologies (iJIM), 2019)
The outcomes of modern technology have turned real-world interaction into a virtual community, then into a cloud one. These giant leaps aided by the excitement created by the possibilities inherent in learning through handheld technologies made using mobile devices in English language teaching (ELT) indispensable. This paper is aimed to deeply overview available handheld technologies and their features that can enable teachers in their mission. It investigates the synergy of a group of mobile devices of smartphones, tablets, iPods, iPads, E-readers, and classroom response systems, among others. These devices have been effective in everyday activities, and are expected to enrich ELT, especially in communities where there is a lack of community of practice (CoP) on the target language. To this aim, this paper was cored around reviewing the potential handheld technologies have in language classrooms. The main data were obtained from the rich body of literature, shedding more light on their properties in creating interactive communication in and out of classrooms. The findings revealed that handheld technologies can be successfully integrated into English language teaching and learning. Pedagogically, teachers are encouraged to exploit mobile devices into their classroom practices after closely testing their specifications, and scanning their advantages and shortcomings.